QuickTime for .NET and COM developers - Cromie, John, 1961- (Amsterdam ; Boston : Morgan Kaufmann/Elsevier, 2006)
At the heart of Apple's hugely popular iLife software suiteiMovie, iPhoto, iDVD, GarageBand, and iTunesis QuickTime, the powerful media engine that drives elegant applications for managing movies, images, and audio files. The enduring success of QuickTime is in no small part attributable to its component architecture. This key feature has allowed it to embrace emerging digital media technologies and standards one by one as they have appeared over the 12 or so years since its launch. None of the competing technologies even comes close, let alone on both Mac OS X and Windows. QuickTime for .NET and COM Developers is the first guide to QuickTime for developers using popular RAD tools such a Visual Basic .NET, CΔ, and Visual Basic 6. A general introduction to QuickTime is followed by a detailed explanation of the QuickTime architecture from a.NET and COM perspective, liberally accompanied by code snippets. A number of implementation examples illustrate key QuickTime features, ranging from a simple movie player to a sophisticated interactive application. Also covered is QuickTime scripting in both QuickTime Player (using Windows Scripting) and in Microsoft Office applications (using VBA). Brief guides to developing with QuickTime in Delphi and ATL/WTL are also included. Part of the official Quicktime Developer Series, publishing the finest books on QuickTime in cooperation with Apple. * The first book on QuickTime for .NET and COM application and scripting developers * Written by one of the architects of Apple's QuickTime ActiveX/COM control * Offers numerous sample applications and code examples.
Preface; Chapter 1. Introduction; Chapter 2. Getting Started with the QuickTime Control; Chapter 3. Using the QuickTime Control; Chapter 4. The QuickTime Object Model; Chapter 5. Diving Deeper; Chapter 6. Create and Edit; Chapter 7. Browsing the Media; Chapter 8. Scripting QuickTime Player; Chapter 9. QuickTime meets Office; Appendix A. QuickTime COM Library Reference; Appendix B. Additional COM Host Environments; Appendix C. QuickTime Exporter Types; Index.
Includes index.
Keywords: Motion pictures -- Editing -- Data processing; QuickTime; Microsoft .NET Framework; COM (Computer architecture); Electronic books